2016
DOI: 10.1007/s40519-016-0331-3
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive flexibility and decision-making in eating disorders and obesity

Abstract: Considering the executive functions as a transdiagnostic process in ED and obesity could provide explanations for the inability to regulate food intake, present in both ED and obese patients. Implications of these executive impairments in the development and maintenance of ED and obesity are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 43 publications
8
58
1
3
Order By: Relevance
“…However, others found no significant association between performance on the WCST and addiction (125127). With respect to obesity, a recent study reported impaired performance on the WCST in obese individuals compared to individuals with other eating disorders (128). In addition, a meta-analysis (121) and systematic review (118) both reported impaired WCST performance in obese individuals compared to controls.…”
Section: Neurocognitive Tasksmentioning
confidence: 99%
“…However, others found no significant association between performance on the WCST and addiction (125127). With respect to obesity, a recent study reported impaired performance on the WCST in obese individuals compared to individuals with other eating disorders (128). In addition, a meta-analysis (121) and systematic review (118) both reported impaired WCST performance in obese individuals compared to controls.…”
Section: Neurocognitive Tasksmentioning
confidence: 99%
“…Se trata de un estudio piloto realizado con solo 5 participantes, todas mujeres, y no hemos contado con un grupo control con el que poder contrastar los resultados. Por otra parte, tampoco podemos comparar los resultados con una muestra normativa de referencia completamente adecuada a las características sociodemográfi cas de nuestras participantes, ni contamos con baremos especí-fi cos de ejecución en población obesa, aunque ya empiezan a haber estudios que facilitan la ejecución media en estas pruebas en este tipo de pacientes, siendo semejante a lo que aquí hemos encontrado (Fagundo et al, 2012;Perpiñá et al, 2017). Otra de las limitaciones ha sido no haber podido recoger medidas intermedias, lo cual nos hubiera permitido contar con un diseño de línea base múltiple que hubiera dado más fortaleza a los datos obtenidos.…”
Section: Discussionunclassified
“…Por ejemplo, teniendo en cuenta la difi cultad que estos pacientes presentan para inhibir la ingesta y frenar sus impulsos frente a los alimentos considerados «palatables» o apetitosos (Gionta, 1995) se ha llegado a conceptualizar la obesidad como una adicción a la comida (Gearhardt, Frilo, Dileone, Brownell, y Potenza, 2011). Otras investigaciones se han centrado en el estudio de las funciones ejecutivas y han demostrado que los pacientes con obesidad presentan problemas en la capacidad de tomar decisiones (Daniel, Stanton, y Epstein, 2013;Qavam, Anisan, Fathi, y Pourab, 2015), difi cultades para demorar la gratifi cación a corto plazo a pesar de las consecuencias que puedan existir a largo plazo (Perpiñá, Segura, y Sánchez, 2017), y difi cultades en la capacidad para planifi car y solucionar problemas (Qavam et al, 2015). Todos estos défi cits signifi can un obstáculo para la pérdida de peso y su mantenimiento, ya que cambiar los hábitos de ingesta y actividad implica, entre otros aspectos, ser capaz de cambiar las conductas en función de las consecuencias.…”
Section: Introductionunclassified
“…More perseverative errors are considered as an outcome of worse shifting ability (Berg, 1948). Obesity has been associated with weaker shifting (Boeka & Lokken, 2008;Fitzpatrick, Gilbert, & Serpell, 2013;Perpiñá, Segura, & Sánchez-Reales, 2016;Verdejo-García et al, 2010;Wu et al, 2014). Perseverating in unhealthy eating patterns such as overeating could be viewed as being stuck in unhealthy eating habits (Voon, 2015).…”
Section: Inhibitionmentioning
confidence: 99%
“…For instance, flexible behavioral patterns might be beneficial if it helps someone to take advantage of unexpected opportunities to pursue his or her goals (Bayuk, Janiszewski, & Leboeuf, 2010). We know from previous research that an elevated Body Mass Index (BMI) is associated with weaker EF, including shifting (Boeka & Lokken, 2008;Fagundo et al, 2012;Fergenbaum et al, 2009;Fitzpatrick et al, 2013;Perpiñá et al, 2016;Verdejo-García et al, 2010;Wu et al, 2014). Obesity is in essence the result of a positive energy balance, that is, when energy intake (consumption) exceeds energy expenditure.…”
Section: Study 1 Introductionmentioning
confidence: 99%